2021
DOI: 10.3390/polym13030372
|View full text |Cite
|
Sign up to set email alerts
|

Non-Furanic Humins-Based Non-Isocyanate Polyurethane (NIPU) Thermoset Wood Adhesives

Abstract: Predominantly non-furanic commercial humins were used to prepare humin-based non-isocyanate polyurethane (NIPU) resins for wood panel adhesives. Pure humin-based NIPU resins and tannin–humin NIPU resins were prepared, the latter to upgrade the humins’ performance. Species in the raw humins and species formed in the NIPU resins were identified by Matrix Assisted Laser Desorption Ionization Time of Flight (MALDI ToF) spectrometry and Fourier Transform Infrared (FTIR). Humins, fulvic acid and derivatives, humic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Industrial humins as heterogenous macromolecular compounds can be considered furanic lignins and therefore should find sustainable pathways of valorization. This is already the case for so-called non-furanic humins (composed of humic and fulvic substances in soil) that can be processed with tannins to prepare non-isiocyanate wood adhesives [ 18 ]. Recent examples have demonstrated that furanic humins can be employed in substantial amounts to prepare durable wood panels [ 19 ], biobased composites [ 20 ], or foams [ 21 , 22 ] or as a UV shielding agent for thin PVA films [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial humins as heterogenous macromolecular compounds can be considered furanic lignins and therefore should find sustainable pathways of valorization. This is already the case for so-called non-furanic humins (composed of humic and fulvic substances in soil) that can be processed with tannins to prepare non-isiocyanate wood adhesives [ 18 ]. Recent examples have demonstrated that furanic humins can be employed in substantial amounts to prepare durable wood panels [ 19 ], biobased composites [ 20 ], or foams [ 21 , 22 ] or as a UV shielding agent for thin PVA films [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical modification of bio-sourced polyphenol is interesting because of its environmentally friendly traits [8,9]. These syntheses have been conducted by replacing bisphenol A and isocyanate by natural polyphenol or sugar [10][11][12][13][14]. Recently, different studies reported modification of polyphenolic compounds such as catechin and tannins, two flavonoid-type polyphenol compounds, for the synthesis of different polymers [15][16][17][18] presenting antioxidant properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…Diisocyanate vapors and their residuals in the final product can cause some health problems during manufacturing and use [ 8 ], which is why the transition toward a more sustainable synthesis method of PUs is desired. This is evidenced by the extensive range of PU applications (e.g., foams, coatings, adhesives, and varnishes) [ 9 , 10 , 11 , 12 , 13 , 14 ] and their constantly growing global market, which is valued at around EUR 53 billion [ 15 ].…”
Section: Introductionmentioning
confidence: 99%